COMBINATION OF PHOTOCATALIST TiO2 (Titanium Dioxide) AND H2O2 (Hydrogen Peroxide) IN LAUNDRY WASTEWATER TREATMENT - Teuku Muhammad Ashari; Marlisa; Yeggi Darnas; Khairun Nisah (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Any laundry operation will discharge the waste water directly to the water surface, which can lead to pollution in the water. One method that can be used to treat laundry wastewater is a photocatalytic method with TiO2 (Titanium Dioxide) as an UV-assisted catalyst that is combined with a strong H2O2 oxidizer to produce OH (hydroxyl radical) to oxidize pollutants. The study aims to determine the differences in pH, TSS, BOD, COD, and Phosphate separation values with combination of TiO2 and H2O2 doses with variations in UV exposure time for 30, 60, and 90 minutes. A good quality TSS level obtained in the 60th minute with a dose of 1 g TiO2 and in combination with 10 ml H2O2 can reduce TSS levels by 20 mg/l from the initial TSS with a residual weight of 180 mg/L. A decrease in the quality COD level at a 90 minute clearance time with a dosage of 1 gr TiO2, in a combination of 10 ml H2O2, can reduce the COD levels by 32.5 mg/ l from the original COD value of 89.1 mg/l. A reduction in the phosphate level achieved at the cleaning time of 30 minutes at a combined dose of 4 gr TiO2 in a 40 ml combination, can lower the phosphatic level by 0.05 mg /l from the starting value of 5.61 mg/l and already meet the quality standard of laundry waste water.